Shop (Seoul, Korea Archiworld Co., Ltd, 2010)
This series provides an overall view of a particular space and will be used as a practical interior reference not only to the professionals but also to the public
The book written with English and Korean languages
1
Keywords: Architecture -- Korea; Furniture design; Interior decoration